Development and validation of the work meaning inventory - Tak, Jinkook; Seo, HyungJoon; Kim, HyeSeon; Nam, DongYup; Jung, HeeJung; Kwon, Nuri; Kim, SoYoung; Jung, Iljin (Korean Journal of Industrial and Organizational Psychology, 2015)
The purpose of this study was to develop and validate the Work Meaning Inventory(WMI). 86 items and 9 factors of the inventory were obtained based on open-ended questionnaires from 88 workers. Two preliminary on-line surveys from 500 and 236 employees, respectively, were carried to analyze factor structure of the WMI. The final result showed that the 8 factor model with 54 items was appropriate. Finally, to test the validity of the WMI, the main on-line survey was carried and the questionnaires were collected from 1016 employees across a wide variety of companies. In order to check cross-validity of the inventory, the total group was divided into two sub-groups (each group with 508 employees). The results of factor analyses with group 1 showed that the 8-factor model with 47 items was appropriate. Also the results of confirmatory factor analysis with group 2 showed that the 8-factor model fit the data well. Final 8 factors were as follows: 1) interpersonal relation, 2) economic means, 3) recognition, 4) family support, 5) enjoyment seeking, 6) growth opportunity, 7) society contribution, and 8) life vitality. The WMI was significantly correlated with various criteria such as life satisfaction, life meaning, flourishing, and mental health. Finally, implications and limitations of this study and the directions for future study were discussed.